Difficulty Index and Cognitive Skills of English Textbook for Senior High School - Muslih Hambali; Soni Mirizon; Nandang Heryana (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
This study explored the difficulty index, the terms for the category for reading text level, and cognitive levels of reading texts in the English textbook, Interlanguage, for Senior High School grade 12. The primary aim was to determine the extent to which the degree of the available different categories of reading text levels included the cognitive level of questions. Through the readability test formulas for difficulty index and a checklist based on revised Bloom Taxonomy for cognitive skills, 11 reading texts completed with 56 reading comprehension questions were analyzed. The result revealed that the Interlanguage textbook contained four different categories of reading level such as difficult, fairly difficult, plain, and fairly easy to read. The textbook had in the average category of fairly difficult to read for difficulty index and contained fewer HOTS–based questions than LOTS ones (34% < 66%). Besides, higher reading text levels included fewer HOTS-based questions than those of lower ones. This means a higher level of cognitive skill of questions may appear in any text with a different level of difficulty index. This suggests that the English textbook should be revised to have more HOTS-based question items for developing the students’ high cognitive levels.